2020
DOI: 10.1002/cam4.2800
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of variation in 30‐day mortality following cancer surgeries among older adults across US hospitals

Abstract: Background While public reporting of surgical outcomes for noncancer conditions is common, cancer surgeries have generally been excluded. This is true despite numerous studies showing outcomes to differ between hospitals based on their characteristics. Our objective was to assess whether three prerequisites for quality assessment and reporting are present for 30‐day mortality after cancer surgery: low burden for timely reporting, hospital variation, and potential for public health gains. Study Design We used F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The studies reported the gastric cancer risk correlated with body mass index (BMI) levels in a U-shaped manner, particularly in populations not infected by H. pylori ( Jang et al, 2019 ). The studies have revealed that the cancer surgical death rate differs highly which can be illustrated fortuitously in a treated subset of patients and that accordingly; this variation is the main reason for increased and futile mortality ( Lipitz-Snyderman et al, 2020 ). The quality measurement may be beneficial for the patients to decide value‐based compensatory programs, policy evaluation, and quality battering initiatives with the latest goal of developing patient outcomes ( Lipitz-Snyderman et al, 2020 ).…”
Section: Present Day Standard Therapeutics In Gastric Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…The studies reported the gastric cancer risk correlated with body mass index (BMI) levels in a U-shaped manner, particularly in populations not infected by H. pylori ( Jang et al, 2019 ). The studies have revealed that the cancer surgical death rate differs highly which can be illustrated fortuitously in a treated subset of patients and that accordingly; this variation is the main reason for increased and futile mortality ( Lipitz-Snyderman et al, 2020 ). The quality measurement may be beneficial for the patients to decide value‐based compensatory programs, policy evaluation, and quality battering initiatives with the latest goal of developing patient outcomes ( Lipitz-Snyderman et al, 2020 ).…”
Section: Present Day Standard Therapeutics In Gastric Cancermentioning
confidence: 99%
“…The studies have revealed that the cancer surgical death rate differs highly which can be illustrated fortuitously in a treated subset of patients and that accordingly; this variation is the main reason for increased and futile mortality ( Lipitz-Snyderman et al, 2020 ). The quality measurement may be beneficial for the patients to decide value‐based compensatory programs, policy evaluation, and quality battering initiatives with the latest goal of developing patient outcomes ( Lipitz-Snyderman et al, 2020 ). As the generations change, clinicians are elevating being challenged with the difficulties in treating aged patients, as the number of old aged gastric cancer patients has been rising ( J.I.…”
Section: Present Day Standard Therapeutics In Gastric Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, it aligns with the existing COVID-19 literature, allowing us to place our results in the appropriate context [ 11 ]. Secondly, it is a recognized indicator for assessing healthcare quality [ 12 ], taking into consideration factors such as appropriate procedure performance and complications [ 13 ]. Our analysis showed that there was an increase in 30-day mortality in 2020, not only among infected patients as expected, but also among non-infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Whether or not short-term mortality after the COVID-19 outbreak was due to individual/tumor-related factors, treatment timeliness/clinical decision making or rather misdiagnosed COVID-19 [ 14 ], our data are interesting in several aspects. First, they expand and are in line with recently reviewed studies suggesting that every month delayed in cancer treatment can raise risk of death by around 10% [ 15 ].…”
Section: Discussionmentioning
confidence: 99%